2023
DOI: 10.3390/fishes8080404
|View full text |Cite
|
Sign up to set email alerts
|

Soy Lecithin Supplementation Promotes Growth and Increases Lipid Digestibility in GIFT Nile Tilapia Raised at Suboptimal Temperature

Abstract: Soy lecithin (SL) is a source of phospholipids, which play a crucial role in determining cell membrane structure, fluidity, and functionality. This study investigated the effects of dietary SL on the performance, nutrient digestibility, and body composition of Nile tilapia juveniles (average initial weight 12.2 g) raised at 22 °C. The experimental diets contained increasing levels of SL (0.0, 21.0, 43.0, and 64.0 g kg−1). The best weight gain and feed efficiency occurred with 42.2 and 49.8 g kg−1 of SL inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…At suboptimal temperatures, the addition of phospholipids (4.22% of soy lecithin) improved the weight gain of Nile tilapia (Oreochromis niloticus) reared at 22 • C [45]. For shrimps, a previous study by Zhang et al [46] found better overall health outcomes for P. vannamei on diets containing 10-12% lipids and only 1% dietary lecithin at 28 ± 2 • C. Liou et al [47] observed the best growth and immune responses of P. vannamei at 29.0 ± 1.0 • C with 11% lipids and 1.8% soy lecithin.…”
Section: Growth Performance and Diet Compositionmentioning
confidence: 99%
“…At suboptimal temperatures, the addition of phospholipids (4.22% of soy lecithin) improved the weight gain of Nile tilapia (Oreochromis niloticus) reared at 22 • C [45]. For shrimps, a previous study by Zhang et al [46] found better overall health outcomes for P. vannamei on diets containing 10-12% lipids and only 1% dietary lecithin at 28 ± 2 • C. Liou et al [47] observed the best growth and immune responses of P. vannamei at 29.0 ± 1.0 • C with 11% lipids and 1.8% soy lecithin.…”
Section: Growth Performance and Diet Compositionmentioning
confidence: 99%